2 Strut Allograft is better than 1 in Periprosthetic Total Hip Replacement Fracture? - Lik Han, Ong; Ankimtay, Rutel; Sabaruddin, Abdullah; Reuben, P.R; Faris, Kamaruddin (2025)
Periprosthetic hip fracture is a potentially devastating complication following total hip arthroplasty (THA), with high first-year mortality (15–20%).1 Vancouver B1 generally require open reduction internal fixation with implant with or without strut graft. We report a case of dual strut allograft stabilized with cable ties reconstruction in a chronic kidney disease patient with osteoporosis.